PERKEMBANGAN INDUSTRI MARITIM NUSANTARA (KENYATAAN DAN HARAPAN) - Purwanto, Budi (Jurnal Ilmu Manajemen, 2015)
Through Mr.Djuanda Kartawidjaja (13/12/1957) Indonesia declared as an archipelagic nation and accepts this fact by all members of the union of nations. The Indonesian archipelago consists of many islands scattered stretches from Sabang to Merauke divided by the equator between the north and south as well as put together by the sea. Many potential maritime been dug, but more of the potential of marine resources are not optimally exploited. Author investigate it as search from some of article at and compile it from journal, internet, newspaper, etc. finally the case can to evaluate base on the acknowledgment of marine term and condition at Indonesia with wider history, than found have seriously to manage for come to the dream become to world central of maritime. As the background and as empiric data founded to evaluate base on evaluate methodology & development analysis that have summaries is Indonesia with sea territory majority still not maximum yet to explore and not have creating yet the marine acknowledgment to all of Indonesian.